PENGARUH PEMBERIAN PUPUK YANG BERBEDA PADA KULTUR SPIRULINA PLATENSIS DENGAN MEDIA AIR TAWAR - MUTRIPAH, SITI; BADRIYAH, LAILATUL; SARWOKO, SARWOKO; PURWOKO, BAMBANG; HASAN, NURADNIN (Ganec Swara, 2025)
Indonesia is a vast maritime country with abundant aquatic biodiversity. One of the aquatic organisms that has not been optimally utilized is Spirulina platensis. Challenges in cultivation and high costs are among the reasons why Spirulina platensis is still rarely cultivated and utilized. In this experiment, a cultivation technique for Spirulina platensis was carried out using freshwater media with different fertilization treatments. The results of the experiment concluded that Spirulina platensis can grow well in freshwater media with the addition of Walne fertilizer, AB Mix, and POC. Fertilization with AB Mix resulted in the highest cell density growth on the fifth day of treatment, reaching 92,900 units/mL with a biomass of 103 mg/L. These results were higher compared to Walne fertilizer, which achieved 56,680 units/mL with a biomass of 74 mg/L, and POC fertilizer, which reached 43,800 units/mL with a biomass of 57 mg/L